Responsibility of Individuals and Stakeholders for Obesity and a Healthy Diet: Results From a German Survey - Bayer, Sandra; Drabsch, Theresa; Schauberger, Gunther; Hauner, Hans; Holzapfel, Christina (Frontiers in Psychiatry, 2020)
Introduction: Overweight and obesity are thought to be mainly caused by an energy-rich diet and a sedentary lifestyle. The opinions of those with and without obesity about an individual´s and stakeholder´s responsibility for overweight and obesity as well as a healthy diet is rather unclear. Therefore, a survey was conducted to assess the thoughts of persons with and without obesity about the responsibilities for a high body weight and healthy diet. Methods: This telephone-based survey was conducted in Germany. Landline and mobile phone users older than 17 years were quota sampled to represent the German population (n=1,003). Additionally, 354 adults with a body mass index (BMI) ≥ 30 kg/m2 were included in the survey population. Questions on weight management, eating and drinking and anthropometry were asked. Furthermore, the opinions of participants on the responsibility of individuals and stakeholders for obesity and a healthy diet were collected. Data was statistically weighted by age, gender, education, domicile and BMI. Results: Data of 1,357 persons (51.1% female, age: 50.5 ± 18.5 years, 15.9% with BMI ≥ 30 kg/m2) were analyzed. Participants responded that the general causes of a high body weight were excessive low physical activity (82.7%) and caloric intake (80.5%) followed by a lack of will power (72.1%). Almost 90% of the survey population reported that each individual is responsible for his/her own healthy diet. More than 85% of the survey population agreed that a healthy diet in kindergarten and nutrition education at schools should be the preferred approaches when politics take care of a person´s healthy diet. Sub-analyses revealed that BMI, sex, age and education are potential confounders. Conclusion: This German survey showed that the majority of participants indicated that the responsibility for a healthy diet lies with the individual and high body weight is caused by self-controlled attitudes. These results suggest that the survey population underestimates societal and environmental factors that contribute to the development of obesity, which could lead to attitudes that facilitate weight-related stigmatization. Furthermore, survey participants indicated that they would support policy-driven measures that promote a healthy diet.